2010
DOI: 10.1111/j.1439-0531.2009.01476.x
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Onset of Puberty in Gilts of Thrifty Genotype (Iberian Pig)

Abstract: The Iberian pig is an autochthonous breed of the Mediterranean area, reared extensively in the central and southern areas of Spain and Portugal and that is known worldwide for the production of Iberian ham. The characteristics of the Iberian ham are related to its abundance of intramuscular fat, owing to the high capacity of the pig to accumulate fat under its skin and between the muscular fibres. This ability to store excess fat enables survival during periods of scarcity and it has been found in other antiqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…On these bases, piglets born from Alentejano sows are expected to be more mature at birth than those born from conventional sows. Further, similar to the Meishan female (Legault and Caritez, 1983), the onset of puberty occurs earlier in the IB female (González-Añover et al, 2009) than in modern commercial crosses (LW × LR) when fed similarly. This and the greater maturity at birth would indicate that the IB swine is more precocious than conventional swine.…”
Section: Discussionmentioning
confidence: 65%
“…On these bases, piglets born from Alentejano sows are expected to be more mature at birth than those born from conventional sows. Further, similar to the Meishan female (Legault and Caritez, 1983), the onset of puberty occurs earlier in the IB female (González-Añover et al, 2009) than in modern commercial crosses (LW × LR) when fed similarly. This and the greater maturity at birth would indicate that the IB swine is more precocious than conventional swine.…”
Section: Discussionmentioning
confidence: 65%
“…However, there is no clear information about the real impact of this specific cross on the sexual maturation of these animals. For instance, Gonzalez-Añover et al [4] described that the onset of puberty was earlier in Iberian gilts compared to a Large White  Landrace commercial cross which differed from the traditional assumptions.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, Gonzalez-Añover et al [4] concluded that Iberian females can reach puberty before 180 days of age. In our study, the Iberian females showed first estrus behavior at around 160 days of age.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, in the Mediterranean area these commercial breeds coexist with local breeds, used for the production of unique high-quality traditional pork products. These breeds, usually known as fatty-pigs, are smaller in size, have not undergone intense genetic selection and are less productive than modern breeds [2]. Moreover, due to the traditional rearing system, under extensive free-range conditions, they are exposed to harsh environments and seasonal variations in food availability (associated with the development of a thrifty genotype) [3].…”
Section: Introductionmentioning
confidence: 99%